Aplicações das funções afim e quadrática na educação para o trânsito - Anjos, Damião Moreira dos (2015)
This course conclusion work aims to propose an educational alternative in the field of mathematics through applications of quadratic functions and order in traffic education at the same time that suits the High School Reform Project by Law No. 9394/96. Working with traditionally belonging to the school knowledge disciplines for young people arising from the elementary school and contemplating cross-cutting issue from the National Curriculum Parameters, said work aims to contribute to improving the quality of education in that discipline through contextualization and prepare the student the National High School Exam, turning it as part of the knowledge construction process by putting reality and the daily life of the student as fundamental elements, bringing this process as a key element for the study of discipline and cross-cutting theme involvedin this area.